Microstructural evolution and mechanical properties of 316 austenitic stainless steel by CGP - Singh R.; Agrahari S.; Yadav S.D.; Kumar A. (My University, 2025)
In the present work, 316 austenitic stainless steel was deformed employing constrained groove pressing (CGP). The processed samples of 316 austenitic steel were characterized using X-ray diffraction and electron backscattered diffraction. The analysis of XRD patterns confirms the transformation of the austenitic phase into the martensitic phase. The Rietveld refinement employing MAUD software on XRD patterns of deformed samples indicates the decrease in crystallite size with the increase in microstrain and dislocation density, which is also supported by electron backscatter diffraction results. CGP leads to an increase in strength and a decrease in ductility. The enhancement in yield strength, ultimate tensile strength and hardness after CGP is due to the combined effect of increased dislocation density, martensitic transformation, sub-structure formation and reduced crystallite size. The yield strength, ultimate tensile strength, and hardness values have increased from 428 to 1055 MPa, 702–1135 MPa, and 261 to 360 VHN in two passes of CGP, respectively. However, the toughness value is decreased from 566 to 205 J/m3. Modeled yield strength values in different conditions are in reasonable agreement with experimental results. The results of finite element analysis employing DEFORM-3D software are in good agreement with the theoretical analysis of CGP. © 2021 Elsevier B.V.